Elevated serum asprosin and ANGPTL8 gene expression as novel biomarkers for the diagnosis and prognosis of acute coronary syndrome - Abdulah Albreej, Zainulabdin Abdulnabi; Dehghan, Gholamreza; Nourazarian, Alireza; Aslanabadi, Naser; Assadi, Jamshid (Frontiers in Cardiovascular Medicine, 2025)
IntroductionManaging acute coronary syndrome (ACS) remains a major global healthcare concern. Identifying novel biomarkers is crucial to improving early detection and patient classification. Traditional markers such as cardiac troponins have limitations, including delayed detectability in blood samples, necessitating the search for better alternatives. Asprosin and angiopoietin-like protein 8 (ANGPTL8) have recently emerged as potential biomarkers for ACS diagnosis.MethodsThis comparative study included 100 participants, equally divided into ACS patients and healthy controls with matched demographics. Enzyme-linked immunosorbent assay (ELISA) was employed to quantify asprosin concentrations, while real-time polymerase chain reaction (RT-PCR) assessed ANGPTL8 gene expression levels. Receiver operating characteristic (ROC) curve analysis evaluated the diagnostic utility of these biomarkers, and Spearman's correlation was used to examine relationships between variables.ResultsAsprosin levels were significantly elevated in ACS patients (5.27 ± 0.67 ng/ml) compared to healthy individuals (3.82 ± 1.20 ng/ml, P < 0.001). ROC analysis demonstrated high diagnostic performance, with an area under the curve (AUC) of 0.95, 94% detection accuracy, and 85% precision in true negative identification. Similarly, ANGPTL8 expression was markedly increased (P < 0.001), showing an AUC of 0.83, 88% detection accuracy, and 64% specificity. A strong positive correlation was observed between asprosin and ANGPTL8 (r = 0.795, P < 0.0001).DiscussionThe findings highlight the potential of asprosin and ANGPTL8 as promising diagnostic and prognostic markers for ACS. Their high sensitivity and correlation suggest a complementary role in early ACS detection. However, further clinical trials are required to validate these biomarkers in broader patient populations and determine their practical implementation in medical settings.ConclusionAsprosin and ANGPTL8 exhibit strong diagnostic potential in ACS detection, potentially improving early intervention strategies. Future studies should focus on their integration into clinical practice for enhanced patient outcomes.